2018
DOI: 10.1038/s41386-018-0128-3
|View full text |Cite
|
Sign up to set email alerts
|

Fear extinction disruption in a developmental rodent model of schizophrenia correlates with an impairment in basolateral amygdala-medial prefrontal cortex plasticity

Abstract: Schizophrenia patients typically exhibit prominent negative symptoms associated with deficits in extinction recall and decreased ventromedial prefrontal cortex activity (vmPFC, analogous to medial PFC infralimbic segment in rodents). mPFC activity modulates the activity of basolateral amygdala (BLA) and this connectivity is related to extinction. mPFC and BLA activity has been shown to be altered in the methylazoxymethanol acetate (MAM) developmental disruption model of schizophrenia. However, it is unknown if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Dense reciprocal connections between BLA and hippocampus have been previously identified. Notably, impairment of the interconnected circuit between mPFC, hippocampus and BLA had been implicated in anxiety-like behavior (80)(81)(82)(83). Our multivariate results point to higher BLA-hippocampus functional connectivity that cooccurs with lower BLA-PFC functional connectivity in patients with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 60%
“…Dense reciprocal connections between BLA and hippocampus have been previously identified. Notably, impairment of the interconnected circuit between mPFC, hippocampus and BLA had been implicated in anxiety-like behavior (80)(81)(82)(83). Our multivariate results point to higher BLA-hippocampus functional connectivity that cooccurs with lower BLA-PFC functional connectivity in patients with 22q11.2DS.…”
Section: Discussionmentioning
confidence: 60%
“…Abnormal structure and function of lateral PFC, frequently associated with aberrant executive functioning [58,59] and related belief evaluation deficits [25][26][27] are common findings in both DD and SZ patients. Further, a disruption of fear extinction has been found to be associated with altered connectivity between the amygdala and PFC [60][61][62]. In line with this, aberrant PFC and amygdala coupling in DD may be associated with impaired extinction of fear and anxiety, which, in turn, may facilitate the development and persistence of threat.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, a dysregulation in the activity of BLA nucleus has been suggested to have a clear implication in the etiopathogenesis of social dysfunction in ASD (Ferri et al 2016;Hennessey et al 2018). Furthermore, preliminary studies have demonstrated that neuroarchitectural changes occur in the BLA nucleus of persons with SCZ (Williams et al 2016) while dysregulation in functioning of BLA nucleus strongly correlated with a heightened stress and fear sensitivity to sensory inputs (a characteristic often observed in SCZ) in a developmental rodent model of SCZ (Uliana et al 2018). Therefore, it could be hypothesised that some variants in the TMEM74 gene identified in our study influence the brain expression of this gene, altering the functionality of the BLA nucleus and consequently increasing the probability of having a dysfunctional social behaviour.…”
Section: Discussionmentioning
confidence: 99%